2015
DOI: 10.1021/acsami.5b03753
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Assay To Study the Combinatorial Impact of Substrate Properties on Mesenchymal Stem Cell Migration

Abstract: As an alternative to complex and costly in vivo models, microfluidic in vitro models are being widely used to study various physiological phenomena. It is of particular interest to study cell migration in a controlled microenvironment because of its vital role in a large number of physiological processes, such as wound healing, disease progression, and tissue regeneration. Cell migration has been shown to be affected by variations in the biochemical and physical properties of the extracellular matrix (ECM). To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Therefore, we performed a microfluidic study (Wadhawan et al, 2012;Irimia et al, 2007;Boneschansker et al, 2014) to investigate the combined effect of stiffness and chemokine (EGF). While numerous studies have probed the individual effects of physical or chemical factors on cell behaviour (Shukla et al, 2016;Schultz et al, 2015;Takebayashi et al, 2013;Menon et al, 2015;Ogura et al, 2004;Engler et al, 2006), to the best of our knowledge, this work represents the first study to probe the collective influence of these two factors on hMSC migration. Our findings suggested that the basal stiffness-dependent component of cell speed (v E ) was modulated further by the chemokine concentration, and revealed that a gradient generated by an EGF concentration of 1 ng/ml increased cell directionality in a stiffness-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we performed a microfluidic study (Wadhawan et al, 2012;Irimia et al, 2007;Boneschansker et al, 2014) to investigate the combined effect of stiffness and chemokine (EGF). While numerous studies have probed the individual effects of physical or chemical factors on cell behaviour (Shukla et al, 2016;Schultz et al, 2015;Takebayashi et al, 2013;Menon et al, 2015;Ogura et al, 2004;Engler et al, 2006), to the best of our knowledge, this work represents the first study to probe the collective influence of these two factors on hMSC migration. Our findings suggested that the basal stiffness-dependent component of cell speed (v E ) was modulated further by the chemokine concentration, and revealed that a gradient generated by an EGF concentration of 1 ng/ml increased cell directionality in a stiffness-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…While hMSCs have been reported to migrate up rigidity gradients (durotaxis) in vitro (Vincent et al, 2013), their in vivo migration behaviour is likely to be dictated by a combination of various physical cues sensed by them. Indeed, in polydimethylsiloxane (PDMS) microfluidic devices, which provide multiple physical cues (Hou et al, 2011), hMSCs are maximally migratory on substrates of intermediate stiffness, roughness and hydrophobicity (Menon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The controlled modulation of several properties of polydimethylsiloxane (PDMS) microfluidic surfaces such as the stiffness, hydrophobicity, and roughness improved the spreading and migration of bone‐marrow‐derived MSCs (BMSCs). The results suggested that the surface properties need to be optimized to achieve an efficient SC differentiation . Furthermore, a hemodynamic microenvironment was recapitulated using the exertion of combined cyclic strain and fluid shear stress in a microfluidic flow‐stretch chip to stimulate rat MSCs cocultured with vascular endothelial cells (VECs) and to recapitulate the primary mechanical stimulations in cardiovascular systems .…”
Section: Microfluidics For the Controlled Differentiation Of Stem Cellsmentioning
confidence: 99%
“…Other devices have coupled with sensors when measuring intercellular communication of how cytokines can affect cellular processes in downstream culture 94,95 (Fig 3A). Another possibility of these devices is coupling them with other external cues simultaneously, including substrate stiffness 96 or roughness 97 , biochemical gradients 98,99 or even migration inhibitor factors 100 . Three-dimensional devices have also been created to study longer distance cell-cell signaling similar to endocrine signaling, where signaling can induce migration, proliferation, epithelial-mesenchymal transition (EMT), or more 101–103 .…”
Section: Long Distance Communicationmentioning
confidence: 99%